FLAVONOIDS OF POPULUS BALSAMIFERA PLANTS AND THEIR BIOLOGICAL ACTIVITY - А. Т. Таkibayeva,; A. A. Amirchan,; A. T. Kalkenova,; I. V. Kulakov, (Academic Scientific Journal of Chemistry, 2021)
The work is devoted to the chemical studying of the composition of flavonoids of Populus balsamifera, the isolation of individual compounds, and the establishment of their structure. Balsamic poplar plants are a promising source of many biologically active substances, and in particular, flavonoids. From the buds of Populus balsamifera L. identified four flavonoids with antifungal, antimicrobial antioxidant properties and hepatoprotective activity. Data of flavonoids were isolated by extraction on the soxlet apparatus with 95% ethanol by triple thermal extraction at a temperature of 60 °C, followed by thickening on a rotary evaporator. For isolation from the buds of balsamic poplar, the resulting extract was chromatographed on a column with silica gel of the KSK brand 0.31-0.63 microns, using petroleum ether as eluents petroleum ether-ethyl acetate in various ratios and ethyl acetate. The structure of the isolated compounds was determined by IR, UV, NMR 13C, 1 H spectroscopy. The biological activity of the isolated flavonoids was also studied